The Analysis of Community Satisfaction Index at the Population and Civil Registration Service (Disdukcapil) of Central Bengkulu Regency - Anita Sari;; Sulisti Afriani; Nenden Restu Hidayah (Universitas Dehasen Bengkulu, 2023)
Generally, public service problems can be seen from the low skills of the apparatus and the lack of work equipment, causing uncertain and imprecise service schedules and impacting community satisfaction in public services. Community Satisfaction Index (IKM) is one of the methods used to determine the quality of public services through public perceptions. This study aims to determine the index of community satisfaction with health services at the Population and Civil Registration Service (Disdukcapil) of Central Bengkulu Regency. The analytical method used is the Community Satisfaction Index (IKM) with 9 service elements in accordance with Permenpan and Bureaucratic Reform No. 14 of 2017. Samples in this study were 226 respondents. The results showed that the service satisfaction of the Population and Civil Registration Service (Disdukcapil) of Central Bengkulu Regency was good, this can be seen from the high IKM score of 84.398 which is included in the service quality category is